Comparison of various criteria in interpreting end of therapy F-18 labeled fluorodeoxyglucose positron emission tomography/computed tomography in patients with aggressive non-Hodgkin lymphoma. Issue 4 (April 2013) - Manohar, Kuruva; Mittal, Bhagwant Rai; Raja, Senthil; Bhattacharya, Anish; Malhotra, Pankaj; Varma, Subhash
Abstract Various interpretation criteria exist to assess end of therapy F-18 labeled fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) in lymphoma. This study was carried out to compare these criteria. Data of 69 patients with aggressive non-Hodgkin lymphoma (AGR-NHL) who underwent FDG PET/CT at the end of therapy and were followed up for a minimum period of 1 year (median follow-up period 17 months) were evaluated. Twenty-eight of the 69 patients were found to have residual/recurrent disease during follow-up. The accuracy for predicting residual disease of International Harmonization Project (IHP) criteria, London criteria and Gallamini criteria was 71.0%, 84.0% and 88.4%, respectively. Gallamini and London criteria had greater accuracies in predicting residual disease than IHP criteria (p = 0.0001). The major difference in accuracy was due to the low positive predictive value of IHP criteria. Positive predictive values (PPVs) of both London and Gallamini criteria (79.3% and 88.5%, respectively) were high when compared with that of IHP criteria (60.5%) (p = 0.001). Negative predictive values (NPVs) were similar for all the criteria. In conclusion, Gallamini and London criteria had higher accuracy when interpreting end of therapy FDG PET/CT studies in AGR-NHL. London criteria can be used preferentially over Gallamini criteria because of simplicity in interpretation and reproducibility.